Developing a Food Exposure and Urine Sampling Strategy for Dietary Exposure Biomarker Validation in Free‐Living Individuals. Issue 14 (17th June 2019) - Lloyd, Amanda J.; Willis, Naomi D.; Wilson, Thomas; Zubair, Hassan; Xie, Long; Chambers, Edward; Garcia‐Perez, Isabel; Tailliart, Kathleen; Beckmann, Manfred; Mathers, John C.; Draper, John
Abstract : Scope: Dietary choices modulate the risk of chronic diseases and improving diet is a central component of public health strategies. Food‐derived metabolites present in urine could provide objective biomarkers of dietary exposure. To assist biomarker validation, this work aims to develop a food intervention strategy mimicking a typical annual diet over a short period of time and assesses urine sampling protocols potentially suitable for future deployment of biomarker technology in free‐living populations. Methods and results: Six different menu plans comprehensively represent a typical UK annual diet that is split into two dietary experimental periods. Free‐living adult participants ( n = 15 and n = 36, respectively) are provided with all their food, as a series of menu plans, over a period of three consecutive days. Multiple spot urine samples are collected and stored at home. Conclusion: A successful food exposure strategy is established following a conventional UK eating pattern, which is suitable for biomarker validation in free‐living individuals. The urine sampling procedure is acceptable for volunteers and delivered samples suitable for biomarker quantification. The study design provides scope for validation of existing biomarker candidates and potentially for discovery of new biomarker leads, and should help inform the future deployment of biomarker technology for habitual dietary exposure measurement. Abstract : Food‐derived metabolites present in urine could provide objective biomarkers of dietary exposure. A food intervention strategy mimicking a typical diet in free‐living individuals is developed and spot urine sampling protocols are assessed. This study provides scope for validating existing biomarker candidates and discovering new biomarker leads, and should help in deploying biomarker technology for dietary exposure measurement in the future.